2022
DOI: 10.3390/cancers14102359
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Cumulative Doses of Radioiodine in Differentiated Thyroid Cancer Patients with Type 2 Diabetes Mellitus

Abstract: Radioiodine (131I) therapy for differentiated thyroid cancer (DTC) involves exposure of the whole body, including the heart, to ionizing radiation. This exposure to the subsequent risk of heart disease is uncertain, especially in patients with DTC associated with type 2 diabetes mellitus (DTC/+T2DM). The current study aimed to assess the relationship between left ventricular ejection fraction (LVEF), high cumulative 131I dose, and peripheral blood parameters in patients with DTC/−T2DM and DTC/+T2DM. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Current knowledge concerning the impact of radioiodine treatment on cardiovascular function is limited. A recent study conducted by Stanciu et al [21] have investigated cardiovascular effects of radioiodine treatment in DTC in subjects with type 2 diabetes. The study revealed that cumulative 131I dosage was inversely correlated with systolic function in patients with type 2 diabetes but not in those without type 2 diabetes [21].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Current knowledge concerning the impact of radioiodine treatment on cardiovascular function is limited. A recent study conducted by Stanciu et al [21] have investigated cardiovascular effects of radioiodine treatment in DTC in subjects with type 2 diabetes. The study revealed that cumulative 131I dosage was inversely correlated with systolic function in patients with type 2 diabetes but not in those without type 2 diabetes [21].…”
mentioning
confidence: 99%
“…A recent study conducted by Stanciu et al [21] have investigated cardiovascular effects of radioiodine treatment in DTC in subjects with type 2 diabetes. The study revealed that cumulative 131I dosage was inversely correlated with systolic function in patients with type 2 diabetes but not in those without type 2 diabetes [21]. Although we did not assess diabetes in the present study, our results showed that fasting blood glucose levels were similar among DTC patients with and without RAI therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shed light on the cardiovascular implications of cumulative radioiodine doses in individuals with DTC, particularly those with concurrent T2DM. One study highlighted the differential cardiovascular effects of elevated total doses of 131I in people with DTC with and without T2DM, underscoring the need for tailored therapeutic approaches in this patient population [8].…”
Section: Discussionmentioning
confidence: 99%
“…Another investigation delved into the inflammatory response to radioiodine therapy in women, revealing that the interplay between neutrophils and obesity might limit 131I uptake, suggesting a complex association between prescribed radioiodine activity, blood radioactivity, BMI, and inflammatory markers in patients with both DTC and T2DM [9]. Further research explored the role of peripheral circulating free DNA and the platelet-to-lymphocyte ratio in individuals undergoing radioiodine therapy, indicating potential biomarkers for assessing therapy outcomes in this unique cohort [10].…”
Section: Discussionmentioning
confidence: 99%